COMMUNICATION APPROACH PECULIARITIES IN THE PROCESS OF FOREIGN LANGUAGES LEARNING - Герасименко, Ольга; Михальченко, Катерина (SWorldJournal, 2024)
The article is devoted to the study of the communicative approach to the study of English and other foreign languages and the identification of ways to improve the level of language in communication. Specific practical advises for effective use of commun